الجمعيات السياسية والاجتماعية في ولاية طرابلس الغرب 1882 - 1911 - الإسماعيلي، علي حسين نمر; الإبراهيمي، منذر عبيد رضيوي (جامعة ذي قار - كلية الآداب, 2013)
شهدت طرابلس الغرب خلال الفترة 1882 – 1911 تحركا شعبيا قويا في مواجهة الخطر الأوربي المتزايد، وفي مواجهة الواقع الفاسد الذي كانت الدولة العثمانية تعاني منه، تمثل في تأسيس الجمعيات السياسية والاجتماعية، ففي بداية تلك الفترة قامت أول تجربة تنظيمية واعية في البلاد ومع أنها لم تعمر طويلا في ظل السياسة الاستبدادية للدولة العثمانية إلا انها تركت أثارها الواضحة وفي الولاية وبين الأهالي ويمكن اعتبار هذا التحرك بداية اليقظة العربية الحديثة في طرابلس الغرب، وهو وثيق الصلة باليقظة العربية الحديثة التي شهدتها الأجزاء العربية الأخرى في النصف الثاني من القرن التاسع عشر ولا سيما في مصر وبلاد الشام، وعندما حدث الانقلاب العثماني في عام 1908 في إسطنبول والذي أطاح بحكم السلطان عبد الحميد الثاني (1876 - 1909) فتح المجال لتأسيس الجمعيات الثقافية والاجتماعية وإصدار الصحف والمجلات في أرجاء الدولة العثمانية، كان لطرابلس الغرب نصيبها من ذلك الحدث إذ شهدت هي الاخرى تأسيس الجمعيات السياسية والاجتماعية متمثلة بتأسيس فرع لجمعية الاتحاد والترقي في طرابلس الغرب. Tripoli witnessed during the period 1882-1911 a strong popular movement in the face of growing danger EU, and in the face of the corrupt reality that the Ottoman state was suffering from it, represented in the establishment of political and social associations, in the beginning of that period, the first regulatory conscious experience in the country, however it did not last long under the policy authoritarian of the Ottoman Empire, but it left Atherarha clear and in the state and between parents and can be regarded as a move beginning of vigilance modern Arab in Tripoli, which is closely related to vigilance modern Arab witnessed by the Arab sections other in the second half of the nineteenth century, especially in Egypt and the Levant 0 and when it happened coup Ottoman Empire in 1908 in Istanbul, which toppled the Sultan Abdul Hamid II (1876-1909) opened the way for the establishment of cultural associations, social and publication of newspapers and magazines throughout the Ottoman Empire, was Tripoli share of that event, as seen is the other founding political associations and social, represented by the establishment of a branch of Union and Progress in Tripoli 0
Keywords: التاريخ الليبي; ولاية طرابلس الغرب; ليبيا